Sediment dispersal and basin evolution during contrasting tectonic regimes along the western Gondwanan margin in the central Andes. (May 2023) - Calle, Amanda Z.; Horton, Brian K.; García, Raúl; Anderson, Ryan B.; Stockli, Daniel F.; Flaig, Peter P.; Long, Sean P.
Abstract: A >15-20 km-thick succession in southern Bolivia forms the most-complete stratigraphic record in western Gondwana. Upper Neoproterozoic–Carboniferous clastic rocks record ∼300 Myr of marine, nonmarine, and glacially influenced sedimentation in diverse basin systems generated by variable tectonic regimes along the western edge of Gondwana during active and passive-margin conditions. New provenance results help resolve key uncertainties regarding source regions and sediment dispersal patterns. The findings are integrated with spatial variations in stratigraphic thicknesses to evaluate regional patterns of basin subsidence, magmatism, and deformation during long-term evolution of the western Gondwanan margin in the central Andes. Detrital zircon U–Pb geochronological data for 17 sandstone samples reveal sedimentary input from Precambrian cratonic basement provinces and pre-Andean basement, magmatic arc, and fold-thrust belt source regions. The basement age signatures indicate derivation from the flanking Brasiliano (900-560 Ma) and Pampean (650-500 Ma) provinces to the south and east, and the distal Rio de la Plata craton (2400-2000 Ma) along the eastern South American margin ∼1000–1500 km to the southeast. Although the greater Amazonian craton was not a major contributor, subordinate Amazonian signatures from the Sunsás (1300-950 Ma) province to the east and northeast selectively fed the northern basin regions of the central Andes. Despite the lack of Paleozoic igneous rocks in Bolivia, detrital zircons of Ordovician age attest to the pre-Andean influence of the subduction-related Famatinian magmatic arc. Limited Devonian-Carboniferous igneous material was contributed locally from western pre-Andean highlands or regionally by axial northward transport from selected igneous sources in Argentina and Chile. Episodic recycling of Neoproterozoic–Paleozoic basin fill, including a sharp reappearance of Famatinian-age detritus, can be linked to periods of Paleozoic crustal shortening and foreland sedimentation ascribed to Famatinian, Ocloyic, Chañic, or Gondwanide phases of deformation. The spatial distribution of sediment sources along with temporal shifts in sediment routing highlight several stages in the paleogeographic evolution of the western Gondwanan margin preserved in the central Andes. Initial regional subsidence spanned a multiphase Neoproterozoic to early Paleozoic history of Rodinia breakup, Brasiliano-Pampean orogenesis, and post-orogenic back-arc extension prior to final late Paleozoic amalgamation of Gondwana. The early Paleozoic onset of subduction and Famatinian arc magmatism led to high-magnitude subsidence (>10–15 km) likely driven by Ordovician slab rollback in an extensional back-arc basin. Thereafter, intermittent Paleozoic contraction in a poorly understood pre-Andean system (best expressed in the Eastern Cordillera of Bolivia and neighboring segments of northern Argentina and southern Peru) generated transient topographic loads that produced superimposed flexural foreland and successor basin systems. Highlights: Southern Bolivia contains the most-complete stratigraphic record of western Gondwana. Detrital zircon U-Pb ages reveal Neoproterozoic-Paleozoic shifts in sediment sources. Proximal and distal (>1000 km) cratonic sources fed pre-Andean sedimentary basins. Slab rollback in a back-arc basin likely caused >10 km of Ordovician subsidence. Cratonic and Famatinian arc/orogenic sources fed Paleozoic foreland/successor basins.